HEADACHE PROFILE AND ASSOCIATED SYMPTOMS IN INTRACRANIAL TUMORS - Riski Apriady, Adhitya; Wibisono, Yusuf; Nugraha Hermawan, Asep (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
Intracranial tumors are rare in headache sufferers, although headache is common in intracranial tumor patients. This limits the utility of headache symptoms to make a diagnosis, and it's crucial to know whether people with intracranial tumors have specific headache criteria. Other investigations do not support the classic criteria for headache in intracranial tumors, such as progressive, worse in the morning, and exacerbated by Valsalva maneuvers. Clinical studies found that headache as the sole symptom was rare, and only occurred in 2% of patients, hence this study also investigated the prevalence of nausea/vomiting, seizures, loss of consciousness, and motor deficits. This study uses resumes of medical records of patients diagnosed with intracranial tumors and hospitalized in the Department of Neurology, dr. Hasan Sadikin Central General Hospital West Java, Indonesia. While the sampling method in this study was total sampling, by taking all medical record resumes of patients with intracranial tumors from January to December 2018. Headache was a prevalent symptom of intracranial tumors in this study, occurring in 75,3 % of the subjects and was usually accompanied by other symptoms, especially motor deficits (64,5%), loss of consciousness (60,2%), nausea and vomiting (31) 2%), and seizures (23,7%). Patients were most likely to have bilateral headaches (62,5%), and 63,6% of patients who had unilateral headaches had a unilateral intracranial tumor on the same side of the headache. Patients who experienced progressive headaches were 93,5% of patients. While, the most common headache onset in patients with intracranial tumors before hospital admission were; 3-30 days (40,4%) and > 30 days - 6 months (38,5%).